2015
DOI: 10.1073/pnas.1506111112
|View full text |Cite
|
Sign up to set email alerts
|

Visible photoelectrochemical water splitting into H 2 and O 2 in a dye-sensitized photoelectrosynthesis cell

Abstract: A hybrid strategy for solar water splitting is exploited here based on a dye-sensitized photoelectrosynthesis cell (DSPEC) with a mesoporous SnO 2 /TiO 2 core/shell nanostructured electrode derivatized with a surface-bound Ru(II) polypyridyl-based chromophore-catalyst assembly. The assembly, [(4, H 2 ) 2 bpy) 2 Ru(4-Mebpy-4'-bimpy)Ru (tpy) (OH 2 dye-sensitized photoelectrosynthesis cell | water oxidation | core/shell A lthough promising, significant challenges remain in the search for successful strategies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
173
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(175 citation statements)
references
References 31 publications
2
173
0
Order By: Relevance
“…At low P H2O , the SPARC reaction may be starved for hydride equivalents, leading to incomplete reduction of the CO 2 . Surprisingly, a number of FTS studies have shown that deliberate addition of water to the feed can be beneficial in terms of shifting the selectivity toward C 5 + products (14)(15)(16)(17), which indicates that the presence of water, in itself, is not detrimental to the hydrocarbon-chain-forming process. It is not yet clear how the selectivity of the SPARC reaction can be tuned toward lessoxygenated products, but the feedstock ratio is likely to be one key factor.…”
Section: See Retraction Published January 8 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…At low P H2O , the SPARC reaction may be starved for hydride equivalents, leading to incomplete reduction of the CO 2 . Surprisingly, a number of FTS studies have shown that deliberate addition of water to the feed can be beneficial in terms of shifting the selectivity toward C 5 + products (14)(15)(16)(17), which indicates that the presence of water, in itself, is not detrimental to the hydrocarbon-chain-forming process. It is not yet clear how the selectivity of the SPARC reaction can be tuned toward lessoxygenated products, but the feedstock ratio is likely to be one key factor.…”
Section: See Retraction Published January 8 2018mentioning
confidence: 99%
“…Hydrogen, carbon monoxide, C 1 hydrocarbons, and syngas are the most commonly produced fuels and are derived from water or water and CO 2 (6,16,17). Hydrogen produced via the water-splitting reaction (WSR, reaction 1) is arguably the easiest to produce and stores the most energy on a mass basis (kJ/kg); however, it is not a particularly attractive replacement fuel for transportation, due to technological issues with low-volume energy density, safe storage, and transportation (18).…”
mentioning
confidence: 99%
“…The electrode was prepared with a surface-bound Ru(II) polypyridal-based chromophorephotocatalyst assembly having both a light absorber and water oxidation photocatalyst ( Figure 11) [40]. The chromophore-photocatalyst assembly was stabilized on TiO2 surface via atomic layer deposition of Al2O3 or TiO2 to provide long-term water splitting ability even at pH 7 (in phosphate buffer).…”
Section: Review On Dye-sensitized Overall Water Splittingmentioning
confidence: 99%
“…Alibabaei et al [40] developed a dye-sensitized photo electrosynthesis cell (DSPEC) for solar water splitting utilizing a mesoporous SnO2/TiO2 core/shell nanostructured electrode for solar water splitting. The electrode was prepared with a surface-bound Ru(II) polypyridal-based chromophorephotocatalyst assembly having both a light absorber and water oxidation photocatalyst ( Figure 11) [40].…”
Section: Review On Dye-sensitized Overall Water Splittingmentioning
confidence: 99%
See 1 more Smart Citation